Strategi Meningkatkan Kompetensi Maharoh Qiroah dalam Pembelajaran Bahasa Arab di Pondok Pesantren Rofiu Darojah - Hasanal Bulqiyah; Ainur Rofiq Sofa (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The Maharah qiroah learning strategy at Pondok Pesantren Rofiu Darojah plays a crucial role in enhancing students' Arabic reading skills. This study aims to analyze the applied strategies and the challenges faced in improving students' reading competence. A qualitative research method with a descriptive approach was used, involving interviews with the parents’ caregivers, teachers, and students. The findings indicate that the qiroah mufasshiroh, talaqqi, and drill methods are effective in improving students' comprehension and reading fluency. However, challenges remain, such as difficulties in understanding complex sentence structures and a lack of independent reading practice. Therefore, further efforts are needed, including strengthening nahwu and shorof learning, increasing reading practice intensity, and utilizing educational technology. With the implementation of more innovative strategies and full support from educators, students’ reading abilities are expected to improve significantly.